ICTs for advancing rural communities and human development : addressing the digital divide / (Acc. 4716) - Chhabra Susheel (United States of America : Information Science Reference, 2012)
"This book reviews the important impact ICTs have on economic, social, and political development and provides analyses of ICTs for education, commerce, and governance"--
Keywords: Rural development; Information technology; Digital divide